Let-7 microRNA is a critical regulator in controlling the growth and function of silk gland in the silkworm. Issue 5 (3rd May 2020) - Wang, Wei; Wang, Xinran; Luo, Chengyi; Pu, Qian; Yin, Quan; Xu, Lili; Peng, Xinyue; Ma, Sanyuan; Xia, Qingyou; Liu, Shiping
ABSTRACT: The silk gland is characterized by high protein synthesis. However, the molecular mechanisms controlling silk gland growth and silk protein synthesis remain undetermined. Here we demonstrated that CRISPR/Cas9-based knockdown of let-7 or the whole cluster promoted endoreduplication and enlargement of the silk gland, accompanied by changing silk yield, whereas transgenic overexpression of let-7 led to atrophy and degeneration of the silk gland. Mechanistically, let-7 controls cell growth in the silk gland through coordinating nutrient metabolism processes and energy signalling pathways. Transgenic overexpression of pyruvate carboxylase, a novel target of let-7, resulted in enlargement of the silk glands, which is consistent with the abnormal phenotype of the let-7 knockdown. Overall, our data reveal a previously unknown miRNA-mediated regulation of silk gland growth and physiology and shed light on involvement of let-7 as a critical stabilizer and booster in carbohydrate metabolism, which may have important implications for understanding of the molecular mechanism and physiological function of specialized organs in other species.